Menggagas Model Pengembangan Standarisasi Sistem Pendidikan Pesantren - Cahya Setyawan (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
Pesantren in the current era is a portrait of the movement anddevelopment of Islamic education. Pesantren is already a style of Islamiceducation. Image boarding now is not as ancient as the place that impressedtraditional education, but schools are now renew their education systems.Many boarding schools grow up into semi-modern, semi modern like inGontor. Even schools already teach science and tegnologi like Darul ulum.Then automatically schools already have a quality standard that is ideal atthis time. Through this article will explain about thinking dipesantreneducation standards.